Impact of Religious Precepts on Environmental Policies in Urhoboland of Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
This paper analyzes the influence of religious precepts on environmental policies in Urhoboland, Nigeria, emphasizing a deficiency in policies that prioritize Western models over indigenous knowledge. Employing qualitative methodologies such as interviews and content analysis, it demonstrates that the Urhobo holistic worldview integrates spirituality with environmental care. Religious views can facilitate policy acceptability by portraying nature as sacrosanct, yet may obstruct it when secular restrictions conflict with spiritual concepts. The research promotes the incorporation of these values into environmental policies to enhance their efficacy and sustainability, while also advocating for engagement with religious institutions and the integration of indigenous ethics into policy formulation.